2010
DOI: 10.1161/circresaha.109.213702
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sox9 Function Promotes Heart Valve Calcification Phenotypes In Vivo

Abstract: Rationale: Calcification of heart valve structures is the most common form of valvular disease and is characterized by the appearance of bone-like phenotypes within affected structures. Despite the clinical significance, the underlying etiology of disease onset and progression is largely unknown and valve replacement remains the most effective treatment. The SRY-related transcription factor Sox9 is expressed in developing and mature heart valves, and its function is required for expression of cartilage-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 63 publications
(80 reference statements)
10
124
2
1
Order By: Relevance
“…In human osteoblasts and mesenchymal stem cells, Slug is recruited to the Runx2 promoter and upregulates Runx2. Silencing of Slug has been shown to promote expression of the chondrogenic marker Sox9 (29,32), which protects AVICs from calcification (33). We found that slug is transcriptionally regulated by p53 in pAVICs concomitant with increased Runx2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…In human osteoblasts and mesenchymal stem cells, Slug is recruited to the Runx2 promoter and upregulates Runx2. Silencing of Slug has been shown to promote expression of the chondrogenic marker Sox9 (29,32), which protects AVICs from calcification (33). We found that slug is transcriptionally regulated by p53 in pAVICs concomitant with increased Runx2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…Both collagen IV-producing (BM-producing) cardiomyocytes and collagen I-producing (interstitial matrixproducing) cardiac fibroblasts secrete fibrillin 1 and thus cooperate in assembling the interconnected meshwork of myocardial microfibrils (5,7). Lacking suitable fibroblast-specific Cre-driving transgenes, we assessed the role of fibrillin 1 in the myocardium by selectively targeting Fbn1 gene expression in cardiomyocytes using the αMHC-Cre transgenic mouse (Supplemental Figure 2A 36,37). Since an aorta with no fibrillin 1 ruptures soon after birth (38), we interbred hypomorphic Fbn1 Lox/mgR mice with Wnt1-Cre transgenic mice so as to decrease rather than eliminate fibrillin 1 deposition in the aortic media.…”
Section: Dcm Is Part Of the Cardiovascular Phenotype Of Mice With Sevmentioning
confidence: 99%
“…However, miR-145 has been shown to be expressed in various mouse tissues (although cartilage was not tested), being highly abundant in fat and the aorta, and loss of miR-145 induced structural modifications specifically in the proximal aorta, where the aorta emerges from the heart (15). This is intriguing because the aortic valves in the heart express Sox9, which when deleted in the mouse leads to calcification of the aortic valves, the most prominent form of valvular disease (32). Significantly increased expression of Runx2 and other osteogenic markers was detected in these Sox9-deficient aortic valves.…”
Section: Donormentioning
confidence: 99%